Highly selective oxidation of methane to formaldehyde on tungsten trioxide by lattice oxygen - Yingying Fan (Elsevier, 2021)
Photocatalytic oxidation of methane into formaldehyde in high yield and selectivity remains a grand challenge due to the ineluctable intermediates. Here, we report that a {001}, {010} and {100} facets modified tungsten trioxide photocatalyst enables an intermediate-free oxidation of methane into formaldehyde with 99.4% selectivity. A durable formaldehyde yield of 4.61 mmol g−1 can be achieved after irradiation for 30 h. Mechanism studies disclose that surface defect and reactive lattice oxygen atom are crucial for the selectivity and productivity promotion. This work provides a valid paradigm for efficient conversion of methane to formaldehyde.